2009
DOI: 10.1186/1471-2180-9-174
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid production in vitro and plant growth promotion in maize under controlled environment by phosphate-solubilizing fluorescent Pseudomonas

Abstract: BackgroundPhosphorus deficiency is a major constraint to crop production due to rapid binding of the applied phosphorus into fixed forms not available to the plants. Microbial solubilization of inorganic phosphates has been attributed mainly to the production of organic acids. Phosphate-solubilizing microorganisms enhance plant growth under conditions of poor phosphorus availability by solubilizing insoluble phosphates in the soil. This paper describes the production of organic acids during inorganic phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 303 publications
(157 citation statements)
references
References 32 publications
16
125
1
3
Order By: Relevance
“…These results are consistent with the report of earlier studies (Illmer and Schinner, 1995;Whitelaw, 2000;Naik et al, 2008;Vyas and Gulati, 2009) which showed that solubilization of insoluble phosphate sources were mediated specifically by the decreasing pH of the medium. It has been well documented that mineral phosphate solubilization by phosphate solubilizing bacteria strains results from the release of low molecular weight organic acids (Illmer and Schinner, 1995;Kim et al, 1997;Vyas and Gulati, 2009), probably as an interacting effect of their hydroxyl or carboxyl groups that may chelate the cations bound to the phosphate, thereby converting it into soluble forms (Kpomblekou and Tabatabi, 1994;Kim et al, 1997). Gram negative isolates displayed better performance in solubilization of different insoluble inorganic P sources compared to Gram positive phosphate solubilizing bacterial isolates in the study which is in line with the results of previous studies (Muleta et al, 2013;Tripura et al, 2007).…”
Section: Quantitative Analysis Of Phosphates Solubilization Efficiencsupporting
confidence: 83%
See 2 more Smart Citations
“…These results are consistent with the report of earlier studies (Illmer and Schinner, 1995;Whitelaw, 2000;Naik et al, 2008;Vyas and Gulati, 2009) which showed that solubilization of insoluble phosphate sources were mediated specifically by the decreasing pH of the medium. It has been well documented that mineral phosphate solubilization by phosphate solubilizing bacteria strains results from the release of low molecular weight organic acids (Illmer and Schinner, 1995;Kim et al, 1997;Vyas and Gulati, 2009), probably as an interacting effect of their hydroxyl or carboxyl groups that may chelate the cations bound to the phosphate, thereby converting it into soluble forms (Kpomblekou and Tabatabi, 1994;Kim et al, 1997). Gram negative isolates displayed better performance in solubilization of different insoluble inorganic P sources compared to Gram positive phosphate solubilizing bacterial isolates in the study which is in line with the results of previous studies (Muleta et al, 2013;Tripura et al, 2007).…”
Section: Quantitative Analysis Of Phosphates Solubilization Efficiencsupporting
confidence: 83%
“…Several studies indicated that the drop in pH is due to the production of organic acids during bacterial growth (Chen et al, 2006;Muleta et al, 2013;Vyas and Gulati, 2009). The decreasing pH and the production of organic acids resulted in solubilization of a considerable amount of soluble P (Chen et al, 2006).…”
Section: Quantitative Analysis Of Phosphates Solubilization Efficiencmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive and significant correlation between phosphate solubilizing microorganisms and soil organic matter content was previously reported by Venkateswarlu et al (1984). Other researchers (Vyas and Gulati, 2009) also reported decreased soil pH in PSB-inoculated soil and indicated organic acid production of both strains. Soil pH reduction was found to be much lower than in the culture medium (Table 1), which could be due to the buffering nature of the soil used in the experiment (Gyaneshwar et al, 1998).…”
Section: After Inoculationmentioning
confidence: 97%
“…On the other hand, the high level of sugarcane bagasse production after the completion of Khuzestan province projects (three million tons per year) and the problems caused due to its storage require a comprehensive measurement in the direction of its optimized utilization and citric acid production (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%